Aluminum alloy and dyeing method thereof

By controlling the vanadium content and classification treatment in aluminum alloy, combined with degreasing, chemical polishing and anodizing steps, the problems of uneven dyeing and chromatic aberration of aluminum alloys are solved, which improves the dyeing yield and reduces production costs.

CN119307995APending Publication Date: 2025-01-14HONGFUJIN PRECISION ELECTRONICS ZHENGZHOU
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411292538.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

During the dyeing process, aluminum alloys often experience uneven dyeing and large color difference range, resulting in low dyeing yield. The existing solutions rely on high-cost precision automation equipment and have a small scope of application.

Method used

By controlling the vanadium content in aluminum alloy, it is divided into different categories, and classified and treated according to the vanadium content, including degreasing, chemical polishing, anodizing and dyeing, the concentration, temperature and time of different oxidation and dyeing agents are adjusted by using different oxidation and dyeing agents. , reduces dyeing unevenness and chromatic aberration.

Benefits of technology

It improves the dyeing uniformity and dyeing yield of aluminum alloys, reduces production costs, avoids the use of high-cost precision automation equipment, and realizes precise dyeing control under conventional equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307995A_ABST
    Figure CN119307995A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of surface treatment, in particular to an aluminum alloy and a dyeing method thereof. The aluminum alloy comprises the following components in percentage by weight: 0.72%-0.78% of silicon, 0.28%-0.28% of aluminum and the balance of aluminum. 0.14% to 0.2% of iron; 0.01% to 0.02% of copper; 0.015% to 0.025% of manganese; 0.72% to 0.78% of magnesium; not more than 0.02% of vanadium; and the balance of aluminum. The dyeing method comprises the steps that the vanadium content in aluminum alloy is detected, the aluminum alloy is classified according to the vanadium content, the aluminum alloy is divided into a first type of aluminum alloy, a second type of aluminum alloy and a third type of aluminum alloy, and the first type of aluminum alloy, the second type of aluminum alloy and the third type of aluminum alloy are subjected to the following steps that the aluminum alloy is degreased; the degreased aluminum alloy is subjected to chemical polishing; the aluminum alloy subjected to chemical polishing is subjected to anodic oxidation; the aluminum alloy subjected to anodic oxidation is dyed; and the dyed aluminum alloy is subjected to hole sealing. According to the aluminum alloy and the dyeing method thereof, the problems of uneven dyeing, large color difference range and the like in the dyeing process can be effectively solved, and the production cost can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of surface treatment technology, and in particular to an aluminum alloy and a dyeing method thereof. Background Art

[0002] Aluminum alloy is a common metal material, which is often used to produce electronic equipment casings, automobile structural parts or handicrafts. When using aluminum alloy to produce various products, it is often necessary to dye its surface to make these products have an aesthetically pleasing appearance.

[0003] When dyeing aluminum alloy products, problems such as uneven dyeing and large color difference range will occur, resulting in low dyeing yield. In order to solve these problems, the current commonly used solution is to use precision automation equipment to accurately control the dyeing steps, so as to adjust the dyeing solution concentration, temperature, dyeing time, etc. according to the real-time dyeing effect, thereby reducing the problems of uneven dyeing and large color difference range. However, these precision automation equipment are often expensive and have a small scope of application. Summary of the invention

[0004] In view of the above, it is necessary to propose an aluminum alloy and a dyeing method thereof, which can effectively solve the problems of uneven dyeing and large color difference range in the dyeing process, and can reduce production costs.

[0005] The embodiment of the present application provides an aluminum alloy, in which the compositions of each component by weight percentage are: silicon: 0.72% to 0.78%; iron: 0.14% to 0.2%; copper: 0.01% to 0.02%; manganese: 0.015% to 0.025%; magnesium: 0.72% to 0.78%; vanadium: not more than 0.02%; and the balance is aluminum.

[0006] The above-mentioned aluminum alloy contains vanadium, which is an element that affects dyeing uniformity and produces color difference. By controlling the content of vanadium in the aluminum alloy, the dyeing uniformity of the aluminum alloy during the dyeing process can be improved and the color difference range can be effectively reduced.

[0007] In some embodiments, the aluminum alloy further includes: chromium: not more than 0.01%; zinc: not more than 0.02%; titanium: not more than 0.025%; tin: not more than 0.01%; gallium: not more than 0.02%; calcium: not more than 0.001%; ​​sodium: not more than 0.0005%.

[0008] In some embodiments, the weight percentage of vanadium is 0.0089% to 0.0136%.

[0009] In some embodiments, the weight percentage of vanadium is 0.0118% to 0.0122%.

[0010] The present application embodiment provides another method for dyeing the aluminum alloy, comprising the following steps:

[0011] Detecting the vanadium content in the aluminum alloy, and classifying the aluminum alloy according to the vanadium content, classifying the aluminum alloy with a vanadium content of less than or equal to 0.011% by weight as a first type of aluminum alloy, classifying the aluminum alloy with a vanadium content of greater than 0.011% by weight and less than or equal to 0.0125% by weight as a second type of aluminum alloy, and classifying the aluminum alloy with a vanadium content of greater than 0.0125% by weight and less than or equal to 0.02% by weight as a third type of aluminum alloy, and performing the following steps on the first type of aluminum alloy, the second type of aluminum alloy, and the third type of aluminum alloy, respectively:

[0012] Degreasing the aluminum alloy;

[0013] Chemically polishing the degreased aluminum alloy;

[0014] Anodizing the aluminum alloy after chemical polishing;

[0015] Dyeing the anodized aluminum alloy;

[0016] The dyed aluminum alloy is sealed.

[0017] The above dyeing method detects the vanadium content in the aluminum alloy before dyeing it, classifies the aluminum alloy according to the different vanadium contents, and processes the aluminum alloys with different vanadium contents separately, so as to effectively reduce the phenomenon of uneven dyeing and effectively reduce the color difference range.

[0018] In some embodiments, for the second type of aluminum alloy having a vanadium content greater than 0.011% by weight and less than or equal to 0.0125% by weight, the step of:

[0019] The second type of aluminum alloy after anodization is activated for the first time.

[0020] In some embodiments, after first activating the second type aluminum alloy having a vanadium content greater than 0.011% by weight and less than or equal to 0.0125% by weight, the following steps are further included:

[0021] The second type of aluminum alloy after the first activation is activated for the second time.

[0022] In some embodiments, for the second type of aluminum alloy having a vanadium content of greater than 0.011% by weight and less than or equal to 0.0125%, in the anodizing step, the oxidizing solution is a mixture of sulfuric acid and oxalic acid, the sulfuric acid concentration ranges from 80 g / L to 120 g / L, the oxalic acid concentration ranges from 20 g / L to 40 g / L, the solution temperature ranges from 26° C. to 30° C., the oxidation time ranges from 49 min to 59 min, and the current density ranges from 0.8 A / dm 2 ~1.0A / dm 2 ;

[0023] In the first activation step, the activation solution is aminosulfonic acid, the concentration range of aminosulfonic acid is 36g / L to 60g / L, the solution temperature range is 16°C to 25°C, and the activation time range is 4min to 8min;

[0024] In the second activation step, the activation solution is nitric acid, the concentration range of nitric acid is 1g / L to 5g / L, and the activation time range is 1min to 3min;

[0025] In the dyeing step, the dyeing solution is a blue pigment, the concentration range is 0.8g / L to 1.0g / L, the pH value range is 5.2 to 5.5, the dyeing temperature range is 38°C to 42°C, and the dyeing time range is 280s to 320s.

[0026] In some embodiments, for the first type of aluminum alloy having a vanadium content of less than 0.011% by weight:

[0027] In the anodizing step, the oxidizing solution is a mixture of sulfuric acid and oxalic acid, the sulfuric acid concentration ranges from 80g / L to 120g / L, the oxalic acid concentration ranges from 5g / L to 25g / L, the solution temperature ranges from 24°C to 28°C, the oxidation time ranges from 45min to 55min, and the current density ranges from 0.6A / dm 2 ~0.8A / dm 2 ;

[0028] In the dyeing step, the dyeing solution is a blue pigment, the concentration range is 0.77g / L to 0.97g / L, the pH value range is 5.3 to 5.7, the dyeing temperature range is 28°C to 32°C, and the dyeing time range is 240s to 280s.

[0029] In some embodiments, for the third type of aluminum alloy having a vanadium content of 0.0125% to 0.02% by weight:

[0030] In the anodizing step, the oxidizing solution is a mixture of sulfuric acid and oxalic acid, the sulfuric acid concentration ranges from 80g / L to 120g / L, the oxalic acid concentration ranges from 10g / L to 30g / L, the solution temperature ranges from 25°C to 29°C, the oxidation time ranges from 47min to 57min, and the current density ranges from 0.7A / dm 2 ~0.9A / dm 2 ;

[0031] In the dyeing step, the dyeing solution is a blue pigment, the concentration range is 0.78g / L to 0.98g / L, the pH value range is 5.2 to 5.6, the dyeing temperature range is 32°C to 38°C, and the dyeing time range is 260s to 320s. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 A flow chart of a method for dyeing aluminum alloy provided in an embodiment of the present application.

[0033] Figure 2 This is a flow chart of activating aluminum alloy by the aluminum alloy dyeing method according to an embodiment of the present application.

[0034] Figure 3 This is an electron microscope scanning image of the oxide film when the vanadium content in the aluminum alloy is 0.0136%.

[0035] Figure 4 This is an electron microscope scanning image of the oxide film when the vanadium content in the aluminum alloy is 0.0122%.

[0036] Figure 5 This is an electron microscope scanning image of the oxide film when the vanadium content in the aluminum alloy is 0.0103%.

[0037] Figure 6 This is an electron microscope scanning image of the oxide film when the vanadium content in the aluminum alloy is 0.0089%.

[0038] Figure 7 This is an electron microscope scanning image of the crystal phase of the aluminum alloy when the vanadium content in the aluminum alloy is 0.0136%.

[0039] Figure 8 This is an electron microscope scanning image of the crystal phase of the aluminum alloy when the vanadium content in the aluminum alloy is 0.0122%.

[0040] Fig. 9 This is an electron microscope scanning image of the crystal phase of the aluminum alloy when the vanadium content in the aluminum alloy is 0.0103%.

[0041] Fig.10 This is an electron microscope scanning image of the crystal phase of the aluminum alloy when the vanadium content in the aluminum alloy is 0.0089%. DETAILED DESCRIPTION

[0042] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar components or components with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0043] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0044] The embodiments of the present application are further described below in conjunction with the accompanying drawings.

[0045] The embodiment of the present application provides an aluminum alloy, in which the compositions of each component by weight percentage are: silicon: 0.72% to 0.78%; iron: 0.14% to 0.2%; copper: 0.01% to 0.02%; manganese: 0.015% to 0.025%; magnesium: 0.72% to 0.78%; vanadium: not more than 0.02%; and the balance is aluminum.

[0046] In some embodiments, the aluminum alloy further includes: chromium: not more than 0.01%; zinc: not more than 0.02%; titanium: not more than 0.025%; tin: not more than 0.01%; gallium: not more than 0.02%; calcium: not more than 0.001%; ​​sodium: not more than 0.0005%.

[0047] In some embodiments, the weight percentage of vanadium is 0.0089% to 0.0136%.

[0048] In some embodiments, the weight percentage of vanadium is 0.0118% to 0.0122%.

[0049] The above-mentioned aluminum alloy contains vanadium, which is an element that affects dyeing uniformity and produces color difference. By controlling the content of vanadium in the aluminum alloy, the dyeing uniformity of the aluminum alloy during the dyeing process can be improved and the color difference range can be effectively reduced.

[0050] Adding vanadium (V) to aluminum alloys can significantly improve the mechanical properties and corrosion resistance of aluminum alloys. As an alloying element, vanadium can improve the hardness and tensile strength of aluminum alloys, while improving their corrosion resistance. When the vanadium content in aluminum alloys increases, the hardness, tensile strength and yield strength of the alloy are all improved. In the aluminum alloy dyeing process, a porous oxide film will be formed on the surface of the aluminum alloy after anodizing. This oxide film has strong adsorption and can adsorb organic dyes to achieve dyeing. Since vanadium can improve the microstructure of aluminum alloys, it will affect the formation of oxide film and its ability to adsorb dyes. Controlling the vanadium content in aluminum alloys can improve the uniformity of aluminum alloy dyeing and effectively reduce the color difference range.

[0051] Taking blue dye as an example, aluminum alloys with different element contents were dyed, and the results are as follows:

[0052] Table 1 Effect of different elements on aluminum alloy dyeing

[0053]

[0054]

[0055] It can be seen from Table 1 that the contents of elements such as silicon, iron, copper, manganese, and magnesium have no correlation with the color difference of the aluminum alloy, while the content of vanadium is correlated with the color difference of the aluminum alloy. Specifically, when the vanadium content is low, the aluminum alloy is dyed with blue dye and the color difference is darker and bluer. When the vanadium content is high, the aluminum alloy is dyed with blue dye and the color difference is brighter and yellower.

[0056] Therefore, by controlling the vanadium content in the aluminum alloy, the aluminum alloy can be dyed evenly and with a small color difference under the same dyeing conditions, thereby improving the dyeing yield of the aluminum alloy. At the same time, by controlling the vanadium content in the aluminum alloy, the dyeing effect of the aluminum alloy can be effectively unified. In the actual production process, conventional dyeing equipment can be used to achieve precise control of the dyeing effect of the aluminum alloy, without the need for precision automation equipment, which is conducive to reducing production costs.

[0057] See also Figure 1 and Figure 2 The present application also provides a dyeing method for the aluminum alloy, the dyeing method comprising the following steps:

[0058] Step S1: Detecting the vanadium content in the aluminum alloy, and classifying the aluminum alloy according to the vanadium content, classifying the aluminum alloy with a vanadium content of less than or equal to 0.011% by weight as a first type of aluminum alloy, classifying the aluminum alloy with a vanadium content of greater than 0.011% by weight and less than or equal to 0.0125% by weight as a second type of aluminum alloy, and classifying the aluminum alloy with a vanadium content of greater than 0.0125% by weight and less than or equal to 0.02% by weight as a third type of aluminum alloy, and performing the following steps on the first type of aluminum alloy, the second type of aluminum alloy, and the third type of aluminum alloy, respectively:

[0059] Step S2: degreasing the aluminum alloy.

[0060] In this embodiment, the degreasing method is: adding an acidic degreasing agent into a degreasing tank, then hanging the aluminum alloy into the degreasing tank until it is completely immersed in the degreasing agent, and removing the aluminum alloy from the degreasing tank after degreasing is completed.

[0061] Step S3: chemically polishing the aluminum alloy after degreasing in step 2.

[0062] In this embodiment, the chemical polishing method is: putting the degreased aluminum alloy into a polishing liquid for polishing until the surface is smooth and burr-free. The polishing liquid may contain phosphoric acid, sulfuric acid, nitric acid, boric acid, etc.

[0063] Step S4: anodizing the aluminum alloy after chemical polishing in step S3.

[0064] In this embodiment, the anodizing method is: putting the chemically polished aluminum alloy into an oxidizing solution in an oxidation tank, and then applying electricity until an oxide layer is formed on the surface of the aluminum alloy. In this embodiment, the oxidizing solution includes nitric acid and oxalic acid.

[0065] Step S5: dyeing the aluminum alloy anodized in step S4.

[0066] In this embodiment, the dyeing method is: placing the oxidized aluminum alloy in a dyeing solution in a dyeing tank for immersion dyeing, the dyeing solution can be a blue dye, a yellow dye, a red dye or a dye of other colors, and the main components of the dyeing solution are all dyeing agents commonly used in the aluminum alloy dyeing process. In the embodiment of the present application, the main component of the dyeing solution is blue dye, which is obviously not a limitation of the embodiment of the present application.

[0067] Step S6: sealing the pores of the dyed aluminum alloy.

[0068] In this embodiment, for the second type of aluminum alloy having a vanadium content of greater than 0.011% by weight and less than or equal to 0.0125% by weight, the following steps are further included after anodizing:

[0069] Step S41: performing a first activation on the second type aluminum alloy anodized in step S3.

[0070] Step S42: performing a second activation on the second type aluminum alloy after the first activation in step S41.

[0071] Before dyeing the aluminum alloy, the vanadium content in the aluminum alloy is detected, and the aluminum alloy is divided into three categories according to the vanadium content, and the three categories of aluminum alloys are dyed respectively.

[0072] In the step of anodizing the first type aluminum alloy having a vanadium content of less than or equal to 0.011% by weight, the oxidizing solution is a mixture of sulfuric acid and oxalic acid, the sulfuric acid concentration ranges from 80 g / L to 120 g / L, the oxalic acid concentration ranges from 5 g / L to 25 g / L, the solution temperature ranges from 24° C. to 28° C., the oxidation time ranges from 45 min to 55 min, and the current density ranges from 0.6 A / dm 2 ~0.8A / dm 2 . In this embodiment, the concentration of sulfuric acid can be 80g / L, 85g / L, 90g / L, 95g / L, 100g / L, 105g / L, 110g / L, 115g / L or 120g / L, etc., or any value between 80g / L and 120g / L, which is not limited here. The concentration of oxalic acid can be 5g / L, 10g / L, 15g / L, 20g / L or 25g / L, etc., or any value between 5g / L and 25g / L, which is not limited here. The temperature of the medicine can be 24°C, 25°C, 26°C, 27°C or 28°C, etc., or any value between 24°C and 28°C, which is not limited here. The oxidation time can be 45 min, 47 min, 49 min, 50 min, 51 min, 53 min or 55 min, etc., or any value between 45 min and 55 min, which is not limited here. The current density can be 0.6 A / dm 2 , 0.65A / dm 2 , 0.7A / dm 2 , 0.75A / dm 2 or 0.8A / dm 2 etc., can also be 0.6A / dm 2 ~0.8A / dm 2 Any value between , not limited here.

[0073] When the sulfuric acid concentration in the oxidizing solution is within the range of 80g / L to 120g / L, the oxalic acid concentration is within the range of 5g / L to 25g / L, the solution temperature is within the range of 24℃ to 28℃, the oxidation time is within the range of 45min to 55min, and the current density is within the range of 0.6A / dm2 ~0.8A / dm 2 When the temperature is within the range, the porosity of the oxide film can be reduced, the pore size of the oxide film can be reduced, and the activity of the oxide film can be reduced, thereby reducing the subsequent dyeing speed and improving the uniformity of dyeing.

[0074] If the sulfuric acid concentration in the oxidizing solution is less than 80g / L and the oxalic acid concentration is less than 5g / L, it will not be possible to form a sufficiently dense oxide film, resulting in an increase in porosity. It will also be impossible to effectively control the pore size of the oxide film, resulting in an increase in pore size. The increase in porosity and pore size may accelerate the adsorption of the dye, resulting in a faster dyeing speed, which in turn leads to uneven distribution of the dye in the oxide film, affecting the uniformity of dyeing. If the temperature of the solution is lower than 24°C, the thickness of the oxide film will increase, and the hardness will be high and the porosity will be low, affecting the dyeing performance. The oxidation time is less than 45min and the current density is less than 0.6A / dm 2 , it will result in the inability to form an oxide film of sufficient thickness and quality, affecting the protective performance of the oxide film.

[0075] If the sulfuric acid concentration in the oxidizing solution is greater than 120g / L and the oxalic acid concentration is greater than 25g / L, the dissolution rate of the oxide film will be accelerated, resulting in a thin and soft film with high porosity. Although the adsorption capacity is strong, the hardness and wear resistance are reduced. If the temperature of the solution is higher than 28°C, the generated oxide film may become loose and uneven, sometimes even discontinuous, and have low hardness. If the oxidation time is greater than 55min, after reaching a certain film thickness, the growth rate will slow down and will no longer increase in the end. If the current density is greater than 0.8A / dm2, the dissolution of the film layer may increase due to the influence of Joule heat, resulting in a decrease in the growth rate of the film, and there is a possibility of burning parts.

[0076] In the step of dyeing the first type aluminum alloy having a vanadium content of less than or equal to 0.011% by weight, the dyeing solution is a blue pigment, the concentration range is 0.77g / L to 0.97g / L, the pH range is 5.3 to 5.7, the dyeing temperature range is 28°C to 32°C, and the dyeing time range is 240s to 280s. In this embodiment, the concentration of the blue pigment can be 0.77g / L, 0.82g / L, 0.87g / L, 0.92g / L or 0.97g / L, etc., or any value between 0.77g / L and 0.97g / L, which is not limited here. The pH value can be 5.3, 5.4, 5.5, 5.6 or 5.7, etc., or any value between 5.3 and 5.7, which is not limited here. The dyeing temperature may be 28°C, 29°C, 30°C, 31°C or 32°C, or any value between 28°C and 32°C, and is not limited here. The dyeing time may be 240s, 250s, 260s, 270s or 280s, or any value between 240s and 280s, and is not limited here.

[0077] When the dyeing solution concentration is within the range of 0.77g / L to 0.97g / L, the pH value is within the range of 5.3 to 5.7, the dyeing temperature is within the range of 28°C to 32°C, and the dyeing time is within the range of 240s to 280s, the dyeing speed can be appropriately reduced, the dyeing activity can be reduced, and the uniformity of dyeing of the first type of aluminum alloy can be improved.

[0078] If the concentration of the dyeing solution is less than 0.77g / L, the low concentration of the dyeing solution may not provide enough dye for the oxide film, resulting in uneven dyeing. If the pH value is less than 5.3, it will affect the combination of the dye and the oxide film, resulting in the color not being bright and firm enough. If the dyeing temperature is less than 28°C, it will slow down the movement of the dye molecules, reduce the coloring speed, and make the dyeing effect insufficient. If the dyeing time is less than 240s, the dyeing time will be too short to allow the dye to fully dye the oxide film, resulting in the color being too light or uneven.

[0079] If the concentration of the dyeing solution is greater than 0.97g / L, the color will be too dark, and the color formed will not be the expected color, making it difficult to achieve a uniform and required color. If the pH value is greater than 5.7, it will affect the combination of the dye and the oxide film, reduce the stability and weather resistance of the dyeing, and even cause the dyeing layer to fall off easily. If the dyeing temperature is greater than 32°C, the dye molecules will be adsorbed in the pores of the oxide film too quickly, resulting in the inability to effectively control the dyeing process and causing uneven color. If the dyeing time is greater than 280s, the dye will be deposited too much on the oxide film, causing the dyeing to be too dark, making it difficult to obtain the desired color.

[0080] In the step of anodizing the second type aluminum alloy having a vanadium content of greater than 0.011% by weight and less than or equal to 0.0125%, the oxidizing solution is a mixture of sulfuric acid and oxalic acid, the sulfuric acid concentration ranges from 80 g / L to 120 g / L, the oxalic acid concentration ranges from 20 g / L to 40 g / L, the solution temperature ranges from 26° C. to 30° C., the oxidation time ranges from 49 min to 59 min, and the current density ranges from 0.8 A / dm 2 ~1.0A / dm 2 . In this embodiment, the concentration of sulfuric acid can be 80g / L, 85g / L, 90g / L, 95g / L, 100g / L, 105g / L, 110g / L, 115g / L or 120g / L, etc., or any value between 80g / L and 120g / L, which is not limited here. The concentration of oxalic acid can be 20g / L, 25g / L, 30g / L, 35g / L or 40g / L, etc., or any value between 20g / L and 40g / L, which is not limited here. The temperature of the medicine can be 26°C, 27°C, 28°C, 29°C or 30°C, etc., or any value between 26°C and 30°C, which is not limited here. The oxidation time can be 49 min, 51 min, 53 min, 55 min, 57 min or 59 min, etc., or any value between 49 min and 59 min, which is not limited here. The current density can be 0.8 A / dm 2 , 0.85A / dm 2 , 0.9A / dm 2 , 0.95A / dm 2 or 1.0A / dm 2 etc., can also be 0.8A / dm 2 ~1.0A / dm 2 Any value in between is not limited here.

[0081] When the sulfuric acid concentration in the oxidizing solution is within the range of 80g / L to 120g / L, the oxalic acid concentration is within the range of 20g / L to 40g / L, the solution temperature is within the range of 26℃ to 30℃, the oxidation time is within the range of 49min to 59min, and the current density is within the range of 0.8A / dm 2 ~1.0A / dm 2 When it is within the range, the porosity of the oxide film can be increased and the pores of the oxide film can be enlarged.

[0082] If the sulfuric acid concentration in the oxidizing solution is less than 80g / L, the oxalic acid concentration is less than 20g / L, the solution temperature is lower than 26°C, the oxidation time is less than 49min, and the current density is less than 0.8A / dm 2When the oxide film is too thick, it will lead to insufficient formation of the oxide film, unsatisfactory pore structure, and reduced film quality, which will in turn affect the dyeing properties and the corrosion and wear resistance of the oxide film.

[0083] If the sulfuric acid concentration in the oxidizing solution is greater than 120g / L, the dissolution rate of the oxide film will be accelerated, resulting in a thin and soft film with high porosity. Although the adsorption capacity is strong, the hardness and wear resistance are reduced. If the oxalic acid concentration is greater than 40g / L, the dissolution of the oxide film will increase, affecting its corrosion resistance and wear resistance. If the temperature of the solution is higher than 30°C, the pores of the oxide film will become larger, affecting the sealing quality, and even the oxide film may become powdery. If the oxidation time is greater than 59min, the thickness of the oxide film will increase, but it may also cause the dissolution and destruction of the oxide film. If the current density is greater than 1.0A / dm 2 When the film is heated, the dissolution of the film will increase due to the influence of Joule heat, which will cause the growth rate of the film to decrease and even burn the workpiece.

[0084] In the step of first activation of the second type aluminum alloy having a vanadium content weight percentage greater than 0.011% and less than or equal to 0.0125%, the activation potion is aminosulfonic acid, the concentration range of aminosulfonic acid is 36g / L to 60g / L, the potion temperature range is 16°C to 25°C, and the activation time range is 4min to 8min. In this embodiment, the concentration of aminosulfonic acid can be 36g / L, 40g / L, 44g / L, 48g / L, 52g / L, 56g / L or 60g / L, etc., or any value between 36g / L and 60g / L, which is not limited here. The potion temperature can be 16°C, 18°C, 20°C, 22°C, 24°C or 25°C, etc., or any value between 16°C and 25°C, which is not limited here. The activation time can be 4min, 5min, 6min, 7min or 8min, etc., or any value between 4min and 8min, which is not limited here.

[0085] When the concentration of aminosulfonic acid in the activation solution of the first activation is in the range of 36g / L to 60g / L, the solution temperature is in the range of 16℃ to 25℃, and the activation time is in the range of 4min to 8min, the activity of the oxide film can be effectively improved, thereby improving the speed and uniformity of dyeing.

[0086] If the concentration of aminosulfonic acid in the activation solution is less than 36g / L, it is not enough to effectively remove the oxide layer and impurities on the surface of the aluminum alloy, resulting in insufficient activation and affecting the subsequent dyeing process. If the temperature of the solution is lower than 16°C and the activation time is less than 4 minutes, the temperature and time during the activation process are insufficient, affecting the pore structure of the oxide film, and further affecting the fastness after dyeing, such as washing fastness and rubbing fastness.

[0087] If the concentration of aminosulfonic acid in the activation solution is greater than 60g / L, the solution temperature is higher than 25℃, and the activation time is greater than 8min, it will lead to over-activation, which will increase the pores of the oxide film and affect the uniformity and density of the film. If the solution temperature is too high, especially under the condition of higher concentration of aminosulfonic acid, it will increase the corrosion risk of the aluminum alloy substrate and damage the structure of the oxide film. If the activation time is too long, it will lead to excessive dissolution of the oxide film, reduce the quality and performance of the film, and affect its corrosion resistance and wear resistance. Over-activation will make it difficult for the dye to be evenly colored, affecting the dyeing effect.

[0088] In the step of performing a second activation on the second type aluminum alloy having a vanadium content weight percentage greater than 0.011% and less than or equal to 0.0125%, the activation solution is nitric acid, the concentration range of the nitric acid is 1g / L to 5g / L, and the activation time range is 1min to 3min. In this embodiment, the concentration of the nitric acid can be 1g / L, 2g / L, 3g / L, 4g / L or 5g / L, etc., or any value between 1g / L and 5g / L, which is not limited here. The activation time can be 1min, 1.5min, 2min, 2.5min or 3min, etc., or any value between 1min and 3min, which is not limited here.

[0089] When the concentration of nitric acid in the activation solution for the second activation is in the range of 1g / L to 5g / L and the activation time is in the range of 1min to 3min, the oxide film can be further activated, which is beneficial to further improve the activity of the oxide film and further improve the uniformity of dyeing.

[0090] If the concentration of nitric acid in the activation solution is less than 1g / L and the activation time is less than 1min, the degree of activation will be insufficient, the activity of the oxide film will not be fully enhanced, the dye molecules may not penetrate evenly during dyeing, and the uniformity of the final dyeing effect will be affected.

[0091] If the concentration of nitric acid in the activation solution is greater than 5g / L and the activation time is greater than 3min, it will lead to over-activation. Excessive nitric acid concentration and too long activation time will corrode the oxide film, affecting its integrity and uniformity. Over-activation will change the chemical properties of the oxide film surface, reduce its adsorption capacity for dyes, and affect the dyeing effect.

[0092] In the step of dyeing the second type aluminum alloy having a vanadium content weight percentage greater than 0.011% and less than or equal to 0.0125%, the dyeing solution is a blue pigment, the concentration range is 0.8g / L to 1.0g / L, the pH value range is 5.2 to 5.5, the dyeing temperature range is 38°C to 42°C, and the dyeing time range is 280s to 320s. In this embodiment, the concentration of the blue pigment can be 0.8g / L, 0.85g / L, 0.9g / L, 0.95g / L or 1.0g / L, etc., or any value between 0.8g / L and 1.0g / L, which is not limited here. The pH value can be 5.2, 5.3, 5.4 or 5.5, etc., or any value between 5.2 and 5.5, which is not limited here. The dyeing temperature may be 38° C., 39° C., 40° C., 41° C. or 42° C., or any value between 38° C. and 42° C., and is not limited here. The dyeing time may be 280 s, 290 s, 300 s, 310 s or 320 s, or any value between 280 s and 320 s, and is not limited here.

[0093] When the concentration of the dyeing solution is within the range of 0.8g / L to 1.0g / L, the pH value is within the range of 5.2 to 5.5, the dyeing temperature is within the range of 38°C to 42°C, and the dyeing time is within the range of 280s to 320s, the dyeing speed, dyeing activity, and dyeing uniformity can be increased.

[0094] If the concentration of the dyeing solution is less than 0.8g / L, the low concentration of the dyeing solution may not provide enough dye for the oxide film, resulting in uneven dyeing. If the pH value is less than 5.2, it will affect the combination of the dye and the oxide film, resulting in a less bright color. If the dyeing temperature is less than 38°C, the coloring speed will be reduced, resulting in an insufficient dyeing effect. If the dyeing time is less than 280s, the dyeing time will be too short to allow the dye to fully dye the oxide film, resulting in a light or uneven color.

[0095] If the concentration of the dyeing solution is greater than 1.0g / L, the color will be too dark, making it difficult to achieve a uniform and desired color. If the pH value is greater than 5.5, it will affect the combination of the dye and the oxide film, reduce the stability of the dyeing, and even cause the dyeing layer to fall off easily. If the dyeing temperature is greater than 42°C, the dye molecules will be adsorbed in the pores of the oxide film too quickly, resulting in the inability to effectively control the dyeing process and causing uneven color. If the dyeing time is greater than 320s, the dye will be deposited too much on the oxide film, causing the dyeing to be too dark, making it difficult to obtain the desired color.

[0096] In the step of anodizing the third type aluminum alloy having a vanadium content of greater than 0.0125% by weight and less than or equal to 0.02%, the oxidizing solution is a mixture of sulfuric acid and oxalic acid, the sulfuric acid concentration ranges from 80 g / L to 120 g / L, the oxalic acid concentration ranges from 10 g / L to 30 g / L, the solution temperature ranges from 25° C. to 29° C., the oxidation time ranges from 47 min to 57 min, and the current density ranges from 0.7 A / dm 2 ~0.9A / dm 2 . In this embodiment, the concentration of sulfuric acid can be 80g / L, 85g / L, 90g / L, 95g / L, 100g / L, 105g / L, 110g / L, 115g / L or 120g / L, etc., or any value between 80g / L and 120g / L, which is not limited here. The concentration of oxalic acid can be 10g / L, 15g / L, 20g / L, 25g / L or 30g / L, etc., or any value between 10g / L and 30g / L, which is not limited here. The temperature of the medicine can be 25°C, 26°C, 27°C, 28°C or 29°C, etc., or any value between 25°C and 29°C, which is not limited here. The oxidation time can be 47 min, 49 min, 51 min, 53 min, 55 min or 57 min, etc., or any value between 47 min and 57 min, which is not limited here. The current density can be 0.7 A / dm 2 , 0.75A / dm 2 , 0.8A / dm 2 , 0.85A / dm 2 or 0.9A / dm 2 etc., can also be 0.7A / dm 2 ~0.9A / dm 2 Any value between , not limited here.

[0097] When the sulfuric acid concentration in the oxidizing solution is within the range of 80g / L to 120g / L, the oxalic acid concentration is within the range of 10g / L to 30g / L, the solution temperature is within the range of 25℃ to 29℃, the oxidation time is within the range of 47min to 57min, and the current density is within the range of 0.7A / dm 2 ~0.9A / dm 2 When the temperature is within the specified range, a uniform, dense and high-quality oxide film can be formed on the surface of the aluminum alloy. The oxide film has good wear resistance, corrosion resistance and dye adsorption capacity, which is beneficial to improving the speed and uniformity of dyeing.

[0098] If the sulfuric acid concentration in the oxidizing solution is less than 80g / L, the oxalic acid concentration is less than 10g / L, the solution temperature is lower than 25°C, the oxidation time is less than 47min, and the current density is less than 0.7A / dm2 When the temperature of the solution is too low, the oxide film will not form fully, and the porosity and pore size will not reach the optimal state, thus affecting the uniformity and speed of dyeing. Specifically, low sulfuric acid concentration may make the oxide film thinner and have low porosity, and insufficient oxalic acid concentration may not effectively refine the pores of the oxide film. Too low a temperature of the solution will slow down the chemical reaction rate, resulting in uneven growth of the oxide film. Insufficient oxidation time will prevent the film from reaching the ideal thickness and hardness. Too low a current density will result in slow growth of the oxide film, affecting the uniformity and quality of the film.

[0099] If the sulfuric acid concentration in the oxidizing solution is greater than 120g / L, the oxalic acid concentration is greater than 30g / L, the solution temperature is higher than 29°C, the oxidation time is greater than 57min, and the current density is greater than 0.9A / dm 2 When the surface is too hot, it will cause excessive dissolution, damage and quality degradation of the oxide film, resulting in uneven dyeing.

[0100] In the step of dyeing the third type aluminum alloy having a vanadium content weight percentage greater than 0.0125% and less than or equal to 0.02%, the dyeing solution is a blue pigment, the concentration range is 0.78g / L to 0.98g / L, the pH value range is 5.2 to 5.6, the dyeing temperature range is 32°C to 38°C, and the dyeing time range is 260s to 320s. In this embodiment, the concentration of the blue pigment can be 0.78g / L, 0.83g / L, 0.88g / L, 0.93g / L or 0.98g / L, etc., or any value between 0.78g / L and 0.98g / L, which is not limited here. The pH value can be 5.2, 5.3, 5.4, 5.5 or 5.6, etc., or any value between 5.2 and 5.6, which is not limited here. The dyeing temperature may be 32°C, 33°C, 34°C, 35°C, 36°C, 37°C or 38°C, or any value between 32°C and 38°C, and is not limited here. The dyeing time may be 260s, 270s, 280s, 290s, 300s, 310s or 320s, or any value between 260s and 320s, and is not limited here.

[0101] When the concentration of the dyeing solution is within the range of 0.78 g / L to 0.98 g / L, the pH value is within the range of 5.2 to 5.6, the dyeing temperature is within the range of 32°C to 38°C, and the dyeing time is within the range of 260s to 320s, the uniformity of dyeing of the third type aluminum alloy can be improved.

[0102] If the concentration of the dyeing solution is less than 0.78g / L, the low concentration of the dyeing solution may not provide enough dye for the oxide film, resulting in uneven dyeing. If the pH value is less than 5.2, it will affect the combination of the dye and the oxide film, resulting in a less bright color. If the dyeing temperature is less than 32°C, the coloring speed will be reduced, resulting in an insufficient dyeing effect. If the dyeing time is less than 260s, the dyeing time will be too short to allow the dye to fully dye the oxide film, resulting in a light or uneven color.

[0103] If the concentration of the dyeing solution is greater than 0.98g / L, the color will be too dark, making it difficult to achieve a uniform and satisfactory color. If the pH value is greater than 5.6, it will affect the combination of the dye and the oxide film, reduce the stability of the dyeing, and even cause the dyeing layer to fall off easily. If the dyeing temperature is greater than 38°C, the dye molecules will be adsorbed in the pores of the oxide film too quickly, resulting in the inability to effectively control the dyeing process and causing uneven color. If the dyeing time is greater than 320s, the dye will be deposited too much on the oxide film, causing the dyeing to be too dark, making it difficult to obtain the desired color.

[0104] Adding vanadium to aluminum alloys can significantly improve the mechanical properties of aluminum alloys, including tensile strength and yield strength, making aluminum alloys more suitable for use under high stress and complex working conditions, and can improve the wear resistance and corrosion resistance of aluminum alloys, extending the service life of the material. Vanadium can also regulate the crystal structure of aluminum alloys, change the grain size and phase transition temperature, thereby further optimizing the performance of the material. Vanadium forms Al in aluminum alloys. 11 V, Al 11 V is a refractory compound that plays a role in refining grains during the melting and casting process. Vanadium can refine the recrystallization structure and increase the recrystallization temperature.

[0105] In the alloy phase, vanadium and aluminum form Al 11 V phase, with the increase of vanadium content, the dendrite segregation of aluminum alloy increases, resulting in the gradual differentiation of aluminum alloy into smaller unit cells. As the vanadium content further increases, the dendrite spacing of aluminum alloy shows a parabolic change trend. When the weight percentage of vanadium in the aluminum alloy reaches between 0.0118% and 0.0122%, the crystal phase differentiation is the most precise, and the composition of the generated aluminum alloy is more stable. In the process of forming the anodic film, the anodic film is made more uniform and dense, the film pores are relatively small, and the subsequent anodic dyeing process coloring speed is relatively slow, making the anodic dyeing color difference brighter.

[0106] Table 2 Effect of vanadium content in aluminum alloy on oxide film

[0107]

[0108]

[0109] Please also see Figures 3 to 6 , Figure 3 This is a scanning electron microscope image of the oxide film formed on the aluminum alloy No. 1 in Table 2. Figure 4 This is a scanning electron microscope image of the oxide film formed on the aluminum alloy No. 2 in Table 2. Figure 5 This is a scanning electron microscope image of the oxide film formed on the aluminum alloy No. 3 in Table 2. Figure 6 This is a scanning electron microscope image of the oxide film formed on the aluminum alloy No. 4 in Table 2.

[0110] Table 3 Effect of vanadium content in aluminum alloy on crystal phase

[0111] serial number Numeric Vanadium content Grain size grade Average Intercept 1 Median 0.0136 4.5 67.3 2 Bright 0.0122 4.8 59.9 3 Dark 0.0103 4.3 72.9 4 Dark 0.0089 4.1 78.4

[0112] Please also see Figures 7 to 10 , Figure 7 This is an electron microscope scanning image of the crystal phase of the aluminum alloy No. 1 in Table 3. Figure 8 It is an electron microscope scanning image of the crystal phase of the aluminum alloy No. 2 in Table 3, Fig. 9 It is an electron microscope scanning image of the crystal phase of the aluminum alloy No. 3 in Table 3, Fig.10 This is an electron microscope scanning image of the crystal phase of the aluminum alloy numbered 4 in Table 3.

[0113] When dyeing aluminum alloys containing vanadium, the oxide film formed in the first type aluminum alloy with a vanadium content of less than or equal to 0.011% by weight is thinner and has larger film pores than the oxide films in the second and third types of aluminum alloys. The first type of aluminum alloy has a larger average intercept of the crystal phase and a smaller grain size, resulting in a faster coloring speed during dyeing. Therefore, the dyeing time should be reduced when dyeing the first type of aluminum alloy.

[0114] The second type of aluminum alloy with a vanadium content of more than 0.011% by weight and less than or equal to 0.0125% has an increased oxide film thickness and smaller film pores than the first type of aluminum alloy, and the average crystal phase intercept of the second type of aluminum alloy is smaller and the grain size is increased, resulting in a slow coloring speed during dyeing. Therefore, the dyeing time should be increased when dyeing the second type of aluminum alloy. In the actual production process, it is necessary to improve the dyeing production efficiency. Therefore, before dyeing the second type of aluminum alloy, it is necessary to activate it to improve the dyeing efficiency.

[0115] The third type of aluminum alloy with a vanadium content of more than 0.0125% by weight and less than or equal to 0.02% has an oxide film with a thickness equivalent to that of the second type of aluminum alloy, and the film pores are larger than those of the second type of aluminum alloy. The average intercept of the crystal phase of the third type of aluminum alloy is increased relative to that of the second type of aluminum alloy, and the grain size is reduced, resulting in a fast coloring speed during dyeing. Therefore, no activation is required when dyeing the third type of aluminum alloy, and the dyeing time is reduced.

[0116] The scheme of the present invention will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present invention and cannot be understood as limiting the present invention. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.

[0117] Example 1

[0118] The vanadium content of the aluminum alloy was detected to be 0.091%. The aluminum alloy was degreased and chemically polished, and then anodized. The oxidation solution was a mixture of sulfuric acid and oxalic acid, the sulfuric acid concentration was 100g / L, the oxalic acid concentration was 15g / L, the solution temperature was 26°C, the oxidation time was 50min, and the current density was 0.7A / dm 2 .

[0119] Then, the aluminum alloy after oxidation is dyed. The dyeing solution is a blue pigment with a concentration of 0.87 g / L, a pH value of 5.6, a dyeing temperature of 32° C., and a dyeing time of 280 s.

[0120] Finally, the aluminum alloy is sealed after dyeing.

[0121] In this embodiment, the chemical solution in the oxidation step can reduce the porosity of the oxide film and reduce the pore size of the oxide film. The chemical solution in the dyeing step can reduce the dyeing speed and reduce the dyeing activity. This can improve the dyeing uniformity of the aluminum alloy during the dyeing process and effectively reduce the color difference range.

[0122] Example 2

[0123] The vanadium content of the aluminum alloy was detected to be 0.118%. The aluminum alloy was degreased and chemically polished, and then anodized. The oxidation solution was a mixture of sulfuric acid and oxalic acid, the sulfuric acid concentration was 100g / L, the oxalic acid concentration was 30g / L, the solution temperature was 28°C, the oxidation time was 54min, and the current density was 0.9A / dm 2 .

[0124] The aluminum alloy after oxidation is activated for the first time. The first activation solution is aminosulfonic acid, the concentration of aminosulfonic acid is 40g / L, the temperature of the solution is 20°C, and the activation time range is 6min.

[0125] The aluminum alloy after the first activation is activated for the second time. The second activation solution is nitric acid, the concentration of nitric acid is 3g / L, and the activation time range is 2min.

[0126] The aluminum alloy after the second activation was dyed, the dyeing solution was a blue pigment, the concentration was 0.9 g / L, the pH value was 5.3, the dyeing temperature was 40°C, and the dyeing time was 320 s.

[0127] Finally, the aluminum alloy is sealed after dyeing.

[0128] In this embodiment, the potion in the oxidation step can increase the porosity of the oxide film and increase the pore size of the oxide film. The aluminum alloy is activated twice before the dyeing step to enhance the activity of the oxide film. The potion in the dyeing step can increase the dyeing speed and dyeing activity, thereby improving the dyeing uniformity of the aluminum alloy during the dyeing process and effectively reducing the color difference range.

[0129] Example 3

[0130] The vanadium content of the aluminum alloy was detected to be 0.136%. The aluminum alloy was degreased and chemically polished, and then anodized. The oxidation solution was a mixture of sulfuric acid and oxalic acid, the sulfuric acid concentration was 100g / L, the oxalic acid concentration was 20g / L, the solution temperature was 27°C, the oxidation time was 52min, and the current density was 0.8A / dm 2 .

[0131] The aluminum alloy after oxidation is dyed. The dyeing solution is blue pigment with a concentration of 0.885 g / L, a pH value of 5.5, a dyeing temperature of 35°C, and a dyeing time of 300 s.

[0132] Finally, the aluminum alloy is sealed after dyeing.

[0133] The dyeing method provided in the embodiment of the present application, before dyeing the aluminum alloy, first detects the vanadium content in the aluminum alloy, classifies the aluminum alloy according to the different vanadium contents, and treats the aluminum alloys with different vanadium contents separately, which can effectively reduce the phenomenon of uneven dyeing and effectively reduce the color difference range. The different vanadium contents in the aluminum alloy will lead to different microstructures of the oxide film formed by the aluminum alloy during the oxidation process, which will lead to color differences in the aluminum alloys with different vanadium contents under the same oxidation and dyeing conditions. By classifying the aluminum alloys according to the vanadium content in the aluminum alloy, the aluminum alloys with vanadium contents in the same range use the same oxidation and dyeing conditions, thereby improving the uniformity of dyeing. Specifically, the dyeing speed is appropriately reduced for aluminum alloys with fast dyeing speed, such as the first type of aluminum alloy; the aluminum alloy with a low dyeing speed is activated to increase the dyeing speed, such as the second type of aluminum alloy; the aluminum alloy with a moderate dyeing speed is not activated or the dyeing speed is reduced, such as the third type of aluminum alloy. Through the dyeing method adopted in the embodiment of the present application, the conventional dyeing equipment can be used to achieve accurate control of the dyeing effect of the aluminum alloy, without the need to use precision automation equipment, which is conducive to reducing production costs.

[0134] It is obvious to those skilled in the art that the present application is not limited to the details of the exemplary embodiments described above, and that the present application can be implemented in other specific forms without departing from the spirit or essential features of the present application. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present application is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present application.

[0135] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the preferred embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.

Claims

1. An aluminum alloy, characterized in that: The composition of each component by weight percentage is: Silicon: 0.72% to 0.78%; Iron: 0.14% to 0.2%; Copper: 0.01% to 0.02%; Manganese: 0.015% to 0.025%; Magnesium: 0.72% to 0.78%; Vanadium: not more than 0.02%; the balance is aluminum.

2. The aluminum alloy according to claim 1, characterized in that Also includes: Chromium: not more than 0.01%; Zinc: not more than 0.02%; Titanium: not more than 0.025%; Tin: not more than 0.01%; Gallium: not more than 0.02%; Calcium: not more than 0.001%; ​​Sodium: not more than 0.0005%.

3. The aluminum alloy according to claim 2, characterized in that The weight percentage of vanadium is 0.0089% to 0.0136%.

4. The aluminum alloy according to claim 3, characterized in that The weight percentage of vanadium is 0.0118% to 0.0122%.

5. A method for dyeing an aluminum alloy, characterized in that: The following steps are involved: Detecting the vanadium content in the aluminum alloy, and classifying the aluminum alloy according to the vanadium content, classifying the aluminum alloy with a vanadium content of less than or equal to 0.011% by weight as a first type of aluminum alloy, classifying the aluminum alloy with a vanadium content of greater than 0.011% by weight and less than or equal to 0.0125% by weight as a second type of aluminum alloy, and classifying the aluminum alloy with a vanadium content of greater than 0.0125% by weight and less than or equal to 0.02% by weight as a third type of aluminum alloy, and performing the following steps on the first type of aluminum alloy, the second type of aluminum alloy, and the third type of aluminum alloy, respectively: Degreasing the aluminum alloy; Chemically polishing the degreased aluminum alloy; Anodizing the aluminum alloy after chemical polishing; Dyeing the anodized aluminum alloy; The dyed aluminum alloy is sealed.

6. The dyeing method according to claim 5, characterized in that For the second type of aluminum alloy, the following steps are further included after anodizing: The second type of aluminum alloy after anodization is activated for the first time.

7. The dyeing method according to claim 6, characterized in that After the second type aluminum alloy is first activated, the method further comprises the following steps: The second type aluminum alloy after the first activation is activated for the second time.

8. The dyeing method according to claim 7, characterized in that For the second type of aluminum alloy, in the anodizing step, the oxidizing solution is a mixture of sulfuric acid and oxalic acid, the sulfuric acid concentration ranges from 80g / L to 120g / L, the oxalic acid concentration ranges from 20g / L to 40g / L, the solution temperature ranges from 26°C to 30°C, the oxidation time ranges from 49min to 59min, and the current density ranges from 0.8A / dm 2 ~1.0A / dm 2 ; In the first activation step, the activation solution is aminosulfonic acid, the concentration range of aminosulfonic acid is 36g / L to 60g / L, the solution temperature range is 16°C to 25°C, and the activation time range is 4min to 8min; In the second activation step, the activation solution is nitric acid, the concentration range of nitric acid is 1g / L to 5g / L, and the activation time range is 1min to 3min; In the dyeing step, the dyeing solution is a blue pigment, the concentration range is 0.8g / L to 1.0g / L, the pH value range is 5.2 to 5.5, the dyeing temperature range is 38°C to 42°C, and the dyeing time range is 280s to 320s.

9. The dyeing method according to claim 5, characterized in that For the first type of aluminum alloy: In the anodizing step, the oxidizing solution is a mixture of sulfuric acid and oxalic acid, the sulfuric acid concentration ranges from 80g / L to 120g / L, the oxalic acid concentration ranges from 5g / L to 25g / L, the solution temperature ranges from 24°C to 28°C, the oxidation time ranges from 45min to 55min, and the current density ranges from 0.6A / dm 2 ~0.8A / dm 2 ; In the dyeing step, the dyeing solution is a blue pigment, the concentration range is 0.77g / L to 0.97g / L, the pH value range is 5.3 to 5.7, the dyeing temperature range is 28°C to 32°C, and the dyeing time range is 240s to 280s.

10. The dyeing method according to claim 5, characterized in that For the third category of aluminum alloys: In the anodizing step, the oxidizing solution is a mixture of sulfuric acid and oxalic acid, the sulfuric acid concentration ranges from 80g / L to 120g / L, the oxalic acid concentration ranges from 10g / L to 30g / L, the solution temperature ranges from 25°C to 29°C, the oxidation time ranges from 47min to 57min, and the current density ranges from 0.7A / dm 2 ~0.9A / dm 2 ; In the dyeing step, the dyeing solution is a blue pigment, the concentration range is 0.78g / L to 0.98g / L, the pH value range is 5.2 to 5.6, the dyeing temperature range is 32°C to 38°C, and the dyeing time range is 260s to 320s.

Citation Information

Cited By

  • Method for anodizing aluminum or aluminum alloy and metal workpiece

    TWI942576B